2021
DOI: 10.1111/aji.13404
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of immune‐mediated conditions and endometriosis among adolescents and adult women

Abstract: Problem: Associations between immune dysfunction conditions (eg, systemic lupus erythematous, rheumatoid arthritis) and endometriosis have been observed in adult women, but not assessed among a younger population. We investigated the association between immune-mediated conditions and endometriosis among young women. Method of Study:This cross-sectional analysis in the Women's Health Study: From Adolescence to Adulthood included 551 participants with surgically diagnosed endometriosis (median age=19) and 652 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…Considering that endometriosis was reported to involve Th1/Th2 immune responses, 4–6 other type 1 allergies might also be associated with endometriosis. However, to the best of our knowledge, only two case‐control studies in the 1980s and a cross‐sectional study from the United States investigated this association 24 . In the present study, we found a slightly higher incidence of endometriosis in patients with allergic rhinitis, allergic conjunctivitis, and urticaria, whereas the association was not significant for atopic dermatitis.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Considering that endometriosis was reported to involve Th1/Th2 immune responses, 4–6 other type 1 allergies might also be associated with endometriosis. However, to the best of our knowledge, only two case‐control studies in the 1980s and a cross‐sectional study from the United States investigated this association 24 . In the present study, we found a slightly higher incidence of endometriosis in patients with allergic rhinitis, allergic conjunctivitis, and urticaria, whereas the association was not significant for atopic dermatitis.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies of the association between allergic or autoimmune diseases and endometriosis have reported inconsistent results 17–24 . In a cross‐sectional study by Sinaii et al 17 autoimmune diseases (RA, SLE), allergies and asthma were more common in women with endometriosis than in the general population.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A case-control study of 150 women with endometriosis, SLE, celiac disease, inflammatory bowel disease, and autoimmune thyroiditis was more frequent in those with endometriosis [4]. Another case-control study demonstrated an increasing number of immune-mediated conditions and co-occurring endometriosis [5]. A nationwide population-based study showed an increased risk of RA in patients with endometriosis during more than 10-year follow-up [6].…”
Section: Endometriosis and Autoimmune Diseasesmentioning
confidence: 98%